PENGARUH MINAT TERHADAP AKTIVITAS BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN MATEMATIKA DI SMP KRISTEN ENDE - Maria Sutrisna Sri Ayu Anna; Gregorius Taga; Lely Suryani (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This study aims to determine (1) students' interest in mathematics in class VIII SMP Kristen Ende. (2) Students' learning activities towards mathematics in class VIII of Ende Christian Junior High School. (3) The effect of interest on mathematics learning activities in class VIII of Ende Christian Middle School. This research is associative quantitative research. The subjects of this study were class VIII students with a total sample of 30 people. Factors studied in the form of student interest in student learning activities in mathematics. Data collection methods used in this study were questionnaires and documentation. Data analysis used simple linear regression analysis. The results showed that (1) students' interest in mathematics is 0,843 (84,3 %). (2) The student's learning activity towards learning mathematics is 0,782 (78,2 %). (3) There is a significant effect of the interest variable on the learning activities of class VIII students in mathematics at the Ende Christian Junior High School  23,9 %, while the rest is influenced by other variables. With the regression calculation obtained Y = 32.241 + 0.399 X. The magnitude of the influence of variable X on the Y variable is 0,239 (23,9 %). The significance value of a hypothesis is the truth value of the accepted or rejected hypothesis. Because the value of tcount> t table is .4,221>0,048with a significant value 0,003<0,05, it can be concluded that there is an influence of interest on the learning activities of class VIII students in mathematics at Christian Junior High School Ende.